Conservative Treatment With Mannitol In A Young Adult With Intracerebral Hemorrhage Resulting In Complete Neurological Recovery: A Case Report - Setiawan Dwi Prabandanu; Delta Iswara; Hermanto Hermanto (International Journal of Health Engineering and Technology, 2026)
Intracerebral hemorrhage (ICH) resulting from arteriovenous malformation (AVM) rupture is a neurological emergency associated with increased intracranial pressure, cerebral edema, and a high risk of morbidity and mortality. Although surgical intervention is the standard treatment for selected patients, conservative management may be considered in clinically stable individuals. The role of mannitol in improving outcomes in young patients with AVM-related ICH remains incompletely understood. We report the case of a 22-year-old man who presented with sudden-onset severe headache accompanied by nausea and vomiting. Brain computed tomography revealed a left parieto-occipital intracerebral hemorrhage with intraventricular extension, while subsequent imaging confirmed a ruptured AVM as the underlying cause. The patient was hemodynamically stable and exhibited no significant focal neurological deficits. Conservative treatment consisting of intravenous mannitol, antihypertensive therapy, analgesics, and supportive care was initiated with close neurological monitoring. During hospitalization, the patient's clinical condition progressively improved, with resolution of headache, nausea, and vomiting, accompanied by recovery of consciousness. He was discharged without residual neurological deficits. This case highlights that conservative management with mannitol may achieve favorable neurological outcomes in carefully selected young adults with AVM-related intracerebral hemorrhage. Early diagnosis, appropriate intracranial pressure control, and close clinical monitoring are essential for optimizing patient recovery. Further studies are needed to establish the role of conservative therapy in similar clinical settings.